Cadherin 6 is activated by Epstein–Barr virus LMP1 to mediate EMT and metastasis as an interplay node of multiple pathways in nasopharyngeal carcinoma. (December 2017) - Zuo, L-L; Zhang, J; Liu, L-Z; Zhou, Q; Du, S-J; Xin, S-Y; Ning, Z-P; Yang, J; Yu, H-B; Yue, W-X; Wang, J; Zhu, F-X; et al.
Abstract Nasopharyngeal carcinoma (NPC) is an epithelial malignancy, which is notorious among head-and-neck cancers with its metastatic feature. Epstein–Barr virus (EBV) infection plays a fundamental role in NPC development with the mechanism is not well understood. Here we demonstrate that EBV oncoprotein LMP1 drives EMT and metastasis of NPC by reactivating the adhesion molecule, cadherin 6 (CDH6), which normally occurs in embryogenesis with unknown role in NPC. CDH6 was found to be upregulated in LMP1-positive NPC tissues, and was identified as a target of the epithelium-specific miR-203. LMP1-activated NF-κB transcriptionally repressed the miR-203 expression by binding to the promoter region of miR-203 gene. CDH6 activation in turn induced EMT and promoted metastasis in NPC. CDH6 depletion, NF-κB inhibitor and miR-203 overexpression were able to impair the EMT effects. The miR-203 downregulation in NPC tissues was strongly associated with metastasis clinically. The CDH6 activator, Runt-related transcription factor 2 (RUNX2), was also activated by EBV in the event. For both CDH6 and RUNX2 are components at TGF-β downstream, CDH6 became a node protein for the interplay of multiple signalings including NF-κB and TGF-β. Therefore, the switch-on of miR-203 was important for nasopharyngeal epithelial cells to maintain normal phenotype. This study demonstrates that EBV has evolved sophisticated strategies by driving epithelial cells to obtain malignant features, particularly in NPC metastasis, providing novel biomarkers for the therapy and prognosis of EBV-associated NPC.